Capability in Reading By Using Indonesian as The National Language for Male Children at the Fifth Grade Students of Elementary School: Psycholinguistic Approach - Lilis Rahmawati; Chalimah Chalimah (IAI Darussalam, 2018)
The aim of this research was to investigate whether the male children could use Indonesian in reading well as the national language. This research could show the phenomena of language development in using national language. We conducted a qualitative study. We recorded 5 male students. We were recording them while they were reading the book which the title was ‘frog, where are you?’ by Mercer Mayer. This book only consisted of pictures without any texts. We focused on the students’ ability in producing simplex and complex clauses. The findings showed that the students were good at reading because the finding showed that four students from five students chose to use complex sentences